The role of topotecan in cancer ginecology treatment - A. G. Kedrova; V. V. Kosyy; D. A. Astakhov (Опухоли женской репродуктивной системы, 2017)
The high morbidity, often latent, asymptomatic disease development is not optimal therapy in the first line, causes the development of the frequent recurrence of tumors, requiring second and thirds lines of chemotherapy. The use of topotecan in standard mode is limited by myelosuppression, therefore the new regimes are studied. To reduce the hematologic toxicity is recommended weekly injection of 4 mg/m2 in 1, 8, 15 days of a 28-day cycle of therapy, as its effectiveness is comparable to the effectiveness of the standard 5-day regime. We determined the toxicity and efficacy of combined weekly topotecan and bevacizumab in patients with secondary platinumresistant ovarian, peritoneal, fallopian tube, endometrium and cervix cancer. Patients were treated topotecan 3,5–4 mg/m2 and bevacizumab 7 mg/kg on days 1, 8, and 15 of a 28-day cycle until progressive disease or excessive toxicity. The primary end point was efficacy and toxicity.Combination on weekly topotecan and bevacizumab showed acceptable toxicity and encouraging efficacy in patients with platinum-resistant tumors.